Years of Potential Life Lost for Children and Adults With Congenital Heart Defects: United States, 2007 to 2017 - Wendy N. Nembhard; Suman Maity; Emine Bircan; Maria D. Politis; Elijah H. Bolin; Jun Ying (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Although most children with congenital heart defects (CHDs) live into adulthood, many have increased mortality risk across the lifespan. Little is known about years lost due to premature CHD‐related deaths. We estimated the years of potential life lost (YPLL) among individuals with CHDs in the United States. Methods We used 2007 to 2017 death records from the US National Center for Health Statistics to identify decedents with a CHD listed as the underlying or contributing cause of death. We calculated the average percent change in YPLL and the total, mean, crude, and age‐standardized YPLL overall, by sex, race and ethnicity, and age group. Results Of 28.35 million deaths, 42 158 were CHD‐related. The premature deaths attributed to CHD for individuals younger than 65 years was almost 2.1 million years; of those 169 756 and 124 067 years were lost prematurely for children and adolescents, respectively. Men and women with CHDs had 1.13 million and 941 115 years lost prematurely, respectively. Non‐Hispanic Black individuals and men had the highest age‐standardized YPLL (per 100 000) (95.5 [95% CI, 93.2–97.7] and 74.1 [95% CI, 73.0–75.1]). The overall mean YPLL was 70 years (per 100 000) and non‐Hispanic Black men and women had the highest mean YPLL. During 2007 to 2017, the YPLL average percent change declined by 17.8% overall, but the YPLL for non‐Hispanic Black individuals aged 1 to 4 years (−31.6%) and 35 to 49 years (−24.3%) had the greatest decline. Conclusions Children with CHDs experience significant premature deaths. Non‐Hispanic Black and male individuals experienced the highest burden of premature deaths associated with CHDs. Further research is needed to elucidate these disparities.